2010
DOI: 10.1016/j.jvs.2010.01.035
|View full text |Cite
|
Sign up to set email alerts
|

Uninsured South Florida vascular surgery patients are less likely to receive optimal medical management than their insured counterparts

Abstract: Compliance with optimal medical therapy for secondary risk factor management amongst our vascular surgery patients is low. Uninsured patients are less likely to receive optimal medical therapy than their insured counterparts. This survey provides sobering statistics regarding medical compliance in our population. This issue deserves further study and may indirectly affect outcomes in minority groups that are disproportionately represented in our uninsured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Prior studies of disparities in PAD have focused on utilization rates of lower extremity revascularization by SES or reported rates of optimal medical therapy by insurance status 59 This present study confirms findings similar to other cardiac disease states in that the use of secondary prevention treatments for PAD was lower among those of low SES. This finding highlights an important gap in the quality of care for patients with PAD, especially since the cost of aspirin and generic statins is low and should not pose significant barriers to patient access to these evidence-based therapies.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Prior studies of disparities in PAD have focused on utilization rates of lower extremity revascularization by SES or reported rates of optimal medical therapy by insurance status 59 This present study confirms findings similar to other cardiac disease states in that the use of secondary prevention treatments for PAD was lower among those of low SES. This finding highlights an important gap in the quality of care for patients with PAD, especially since the cost of aspirin and generic statins is low and should not pose significant barriers to patient access to these evidence-based therapies.…”
Section: Discussionsupporting
confidence: 84%
“…While there have been numerous studies investigating disparities in the care of cardiac patients, 24 disparities research in peripheral arterial disease (PAD) has been limited, 59 even though PAD affects over 7 million Americans 10 and disproportionately affects those of lower socioeconomic status (SES). 11,12 Equitable access to inexpensive guideline-recommended secondary preventive therapies has the potential to improve cardiovascular outcomes in this vulnerable population, but whether treatment rates differ across income groups remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Dual eligibility for Medicaid, an indicator of lower SES, is also associated with an increased all-cause mortality rate in patients with PAD after controlling for other factors [ 128 ]. One study of health behaviors in South Florida reported that, when compared with vascular surgery patients with insurance, uninsured patients were less likely to receive optimal medical management for PAD, highlighting room for improvement in the medical management of uninsured patients with PAD [ 129 ]. Interestingly, a retrospective cohort study found that the 2006 Massachusetts Health Care Reform resulted in a substantial diminishment in prior racial and socioeconomic disparities with regard to amputation, revascularization, and severity of disease in patients with PAD [ 130 ], suggesting that expansion of insurance at the state level is a possible solution to combatting the inequities in outcomes of patients with PAD.…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with numerous other studies that have demonstrated suboptimal medical management of patients with cardiovascular and peripheral vascular disease. 1720 This points to a potential area of improvement in the health care system in general – in the optimization of preventive care in this patient group. This will potentially change the natural history of this disease, both with respect to incidence and survival.…”
Section: Discussionmentioning
confidence: 96%